S68 Assessing pulmonary ventilation and treatment response in patients with asthma and COPD using 19F-MRI: results from the LIFT study. (11th November 2022) - Holland, C; Neal, M; Pippard, B; Forrest, I; Burns, G; Sabroe, I; Lawson, R; Fisher, HF; Matthews, JNS; Simpson, AJ; Wild, JM; Thelwall, PE
Abstract : Introduction: Pulmonary ventilation reflects lung physiology, offering insight regarding structural and functional changes associated with respiratory disease. However, in routine clinical practice, such information may only be derived from multiple tests. Here, we demonstrate the utility of 19 F-MRI of inhaled perfluoropropane (PFP) to directly visualise and measure ventilated lung volumes in patients with asthma and COPD, offering 3D whole-lung imaging without the requirement for ionising radiation or hyperpolarised tracer gases. Methods: 35 patients with a physician diagnosis of asthma (BTS/SIGN guideline 1 Step 3 or above), and 20 patients with COPD (GOLD stage 3 or 4), provided written informed consent and were screened for study eligibility across two UK sites. Participants underwent a single MRI scan session involving inhalation of a 79% PFP/21% oxygen gas mixture, after withholding bronchodilator (BD) medication for 12–24 hours. Inhalation sessions comprised 3 deep breaths of gas followed by a maximal-inspiratory breath-hold, during which 19 F-MR ventilation images were acquired. 19 F-MRI and spirometry were performed before and after administration of 2.5 mg nebulised salbutamol. The percentage ventilated lung volume (%VV) was calculated for all 19 F-MR images. Results: Paired samples t -tests revealed a significant difference between pre- and post-BD%VV measurements in patients with asthma (meanpre-BD =86.7%, SD=15.3%; meanpost-BD =91.5%, SD=10.6%; p =0.002) and patients with COPD (meanpre-BD =69.4%, SD=15.9%; meanpost-BD =73.2%, SD=15.1%; p =0.01), respectively (see figure 1a, 1b ). Comparison of%VV with spirometrically-derived FEV1 measurements revealed a strong positive correlation for patients with asthma ( r =0.502, p <0.001) and patients with COPD ( r =0.58, p <0.001), as shown in figure 1c . Conclusions: We have demonstrated that 19 F MRI may be successfully utilised to assess treatment response in patients with respiratory disease, providing regional information on pulmonary ventilation without the requirement for hyperpolarised-gas MRI. The reproducibility of this technique has previously been established in healthy volunteers 1 . This work builds on the potential of 19 F MRI as an attractive clinical tool for monitoring disease progression and response to therapeutic intervention, which may aid diagnosis and treatment options for patients with a variety of respiratory diseases. References: Pippard BJ, et al . Reproducibility of 19 F-MR ventilation imaging in healthy volunteers. Magn Reson Med 2021;Jun;85 (6):3343–3352.